2018
DOI: 10.1002/aur.2000
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in adults with autism spectrum disorder and intellectual disability

Abstract: Sleep problems (SP) are recognized as a common comorbid condition in autism spectrum disorder (ASD) and can influence core autism symptoms and mental and physical health. SPs can be lifelong and have been reported that adults on the autistic spectrum with and without intellectual disability (ID) present SPs (longer sleep latency, frequent night awakenings, and circadian rhythm sleep-wake disorders). A prospective, objective sleep study was conducted in 41 adults with ASD (33 AE 6 years old) and ID and 51 typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 96 publications
1
46
1
Order By: Relevance
“…Notably, increases in self-grooming behavior measured in the home cage persisted regardless of lights-on or -off conditions (Fig. 4c, d), implying that the mutant mice have a sleep disturbance, as is commonly observed in ASD patients [36,37]. These results suggest that a DLG2 deficiency is associated with increased repetitive behavior.…”
Section: A Dlg2 Deficiency Leads To Increased Self-grooming Behaviorsupporting
confidence: 54%
See 1 more Smart Citation
“…Notably, increases in self-grooming behavior measured in the home cage persisted regardless of lights-on or -off conditions (Fig. 4c, d), implying that the mutant mice have a sleep disturbance, as is commonly observed in ASD patients [36,37]. These results suggest that a DLG2 deficiency is associated with increased repetitive behavior.…”
Section: A Dlg2 Deficiency Leads To Increased Self-grooming Behaviorsupporting
confidence: 54%
“…This implies that these mutant mice might have disrupted sleep patterns. Sleep problems commonly occur not only in patients with ASD [36,37], but also in those with movement disorders such as Fig. 4 Dlg2 -/mice display increased self-grooming behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with ID and/or ASD suffer from sleep disturbances (Ballester et al, 2019; Geoffray et al, 2016; van de Wouw et al, 2013; Veatch et al, 2017). A study from 2013 reported 72% of ID patients to have sleep disturbances (van de Wouw et al, 2013), while a more recent study characterized various qualitative components of sleep in ASD patients, and found an increased number of awakenings during the night, sleep onset latency and reduced sleep efficiency (Ballester et al, 2019). Disturbed sleep does not only negatively affect the emotional status and social behavior of patients, but also their cognitive functioning (Geoffray et al, 2016; Veatch et al, 2017).…”
Section: Using Drosophila To Overcome Bottlenecks In Id and Asd Reseamentioning
confidence: 99%
“…Studies in people with autism have identified various abnormalities in REM sleep including immature organization, decreased quantity, abnormal twitches, undifferentiated sleep and REM sleep behavior disorder, which is characterized by the absence of the muscle atonia that is normal during REM sleep. Clinically, the sleep disturbances are significant in both low and high functioning subjects (136138). The pervasiveness of the sleep disturbances noted may be masking their significance to clinicians, who may accept this as part of ASD rather than a symptom demanding some urgency.…”
Section: Sleepmentioning
confidence: 99%